2014
DOI: 10.3389/fneur.2014.00069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of (−)Epicatechin on the Pathology of APP/PS1 Transgenic Mice

Abstract: Background: Alzheimer’s disease (AD) is a multifactorial disorder characterized by the progressive deterioration of neuronal networks. The clearance of Aβ from the brain and anti-inflammation are potential important strategies to prevent and treat disease. In a previous study, we demonstrated the grape seed extract (GSE) could reduce brain Aβ burden and microglia activation, but which polyphenol plays a major role in these events is not known. Here, we tested pharmacological effects of (−)epicatechin, one prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 45 publications
0
17
1
Order By: Relevance
“…In a previous study, Zeng and colleagues (2014) [101] demonstrated the grape seed extract (GSE) could reduce brain amyloid-β burden and microglia activation, but which polyphenol plays a major role in these events is not known. They tested pharmacological effects of (−) epicatechin, one principle polyphenol compound in GSE, on transgenic AD mice.…”
Section: Research On Curcumin In Mouse Models Of Alzheimer’s Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, Zeng and colleagues (2014) [101] demonstrated the grape seed extract (GSE) could reduce brain amyloid-β burden and microglia activation, but which polyphenol plays a major role in these events is not known. They tested pharmacological effects of (−) epicatechin, one principle polyphenol compound in GSE, on transgenic AD mice.…”
Section: Research On Curcumin In Mouse Models Of Alzheimer’s Diseasementioning
confidence: 99%
“…The (−) epicatechin diet did not alter learning and memory behaviors in AD mice. This study has provided evidence on the beneficial role of (−) epicatechin in ameliorating amyloid-induced AD-like pathology in AD mice, but the impact of (−) epicatechin on tau pathology is not clear, also the mechanism needs further research [101]. …”
Section: Research On Curcumin In Mouse Models Of Alzheimer’s Diseasementioning
confidence: 99%
“…[ 9 ] In the amyloid precursor protein/presenilin 1 (APP/PS1) mice model, epicatechin significantly inhibited the deposits of amyloid in the brain and reduced the levels of Aβ in the blood, with no adverse event. [ 11 ] Moreover, epicatechin appears to be well tolerated in relation to viability and systemic toxicity by APP/PS1 mice. Although these studies suggest a promising future for epicatechin application, there have been inconsistencies[ 12 ] in findings and lack of a systematic approach to discover the underlying mechanism.…”
Section: Introductionmentioning
confidence: 99%
“… 9 , 10 The active ingredient that confers these benefits often remains unclear, as most investigations examine whole foods or multiple flavanols 11 , 12 , 13 , 14 in animal models of aging, 15 , 16 cerebrovascular stress 17 or Alzheimer's disease. 18 , 19 , 20 , 21 , 22 As such, a pure flavanol of particular interest is (−)epicatechin (EC), which traverses the blood–brain barrier and may directly affect brain function. 22 , 23 , 24 EC consumption improves memory in mice 24 and snails.…”
Section: Introductionmentioning
confidence: 99%